Perancangan Data Warehouse untuk Mendukung Sistem Pengelolaan Dokumen Digital dan Tugas Akhir Mahasiswa di Perpustakaan Universitas Sriwijaya - Ali Bardadi; Iman Saladin B.Azhar; Muhammad Hidayat; Nurul Afifah (Universitas Sriwijaya, 2022)
Universitas Sriwijaya’s Library currently manages digital documents where the information displayed is still not comprehensive. Therefore, a large data storage area is needed which is able to present the information quickly. So that it can produce more maximum information in the Universitas Sriwijaya library by building a data warehouse. The design of the data warehouse focuses on presenting the final project documents of Universitas Sriwijaya. The method used in designing a data warehouse is Kimball's Nine-Step Methodology. This method is able to present data in accordance with the information needs of digital document data and final project. Based on the Star Schema data model and data analysis using OLAP, the data warehouse is able to integrate data which makes it easier to access various information very quickly and precisely. The implementation of data warehouse hoped that it can be a solution to monitor academic activities of digital documents and the final project documents of Universitas Sriwijaya